TNFα induced up-regulation of Na+,K+,2Cl− cotransporter NKCC1 in hepatic ammonia clearance and cerebral ammonia toxicity - Vitaly I. Pozdeev (Nature Portfolio, 2017)
Abstract The devastating consequences of hepatic failure include hepatic encephalopathy, a severe, life threatening impairment of neuronal function. Hepatic encephalopathy is caused by impaired hepatic clearance of NH4 +. Cellular NH4 + uptake is accomplished mainly by the Na+,K+,2Cl− cotransporter. Here we show that hepatic clearance of NH4 + is impaired in TNFα deficient as well as TNFR1&TNFR2 double knockout mice, which both develop hyperammonemia. Despite impaired hepatic clearance of NH4 +, TNFα deficient mice and TNFR1 deficient mice were protected against acute ammonia intoxication. While 54% of the wild-type mice and 60% of TNFR2 deficient mice survived an NH4 + load, virtually all TNFα deficient mice and TNFR1 deficient mice survived the treatment. Conversely, TNFα treatment of wild type mice sensitized the animals to the toxic effects of an NH4 + load. The protection of TNFα-deficient mice against an NH4 + load was paralleled by decreased cerebral expression of NKCC1. According to the present observations, inhibition of TNFα formation and/or NKCC1 may be strategies to favorably influence the clinical course of hepatic encephalopathy.